Effect of carotid ligation on cerebral blood flow in baboons: 2. Response to hypoxia and haemorrhagic hypertension. Issue 5 (May 1974) - Sengupta, D.; Harper, Murray; Jennett, Bryan
Abstract : Cerebral blood flow (CBF) measurements were carried out in two groups of anaesthetized normocapnic baboons. In the first group of five animals the effect of hypoxia on the CBF before and after ipsilateral carotid artery ligation was studied. The results showed that, although after ipsilateral carotid ligation there was little change in the CBF at normal PaO2, at hypoxia there was only 20% rise in the CBF as compared with an 80% rise before the carotid ligation. In the second group of 10 animals, effects of haemorrhagic hypotension on the CBF after ipsilateral carotid artery ligation were estimated. The results indicated impairment of autoregulatory response of the cerebral circulation.